The role of Sanskrit literature in Indian renaissance - Dharmmaraj Adat; Reeja B. Kavanal (New Bharatiya Book Corporation, 2017)
Contributed research papers on nationalism, chiefly with reference to Sanskrit literature from Kerala, India.